Radix pseudostellariae of Danzhi Jiangtang capsule relieves oxidative stress of vascular endothelium in diabetic macroangiopathy - Zhaohui Fang; Xiu Hu; Zhi Chen; Jing Xie; Di Wu; Yundong Yin; Liangzhen You (Elsevier, 2020)
Aim: Medicinal plants act as an alternative source of anti-diabetic agents. Recently, Danzhi Jiangtang capsule (DJC) has been clinically used for treatment of diabetes, but the effect of DJC on diabetic macroangiopathy remained unclear. The present study investigates the therapeutic role of DJC in diabetic macroangiopathy and elucidates the underlying mechanisms. Methods: Diabetes patients were treated with DJC for 20 weeks. Blood glucose and serum parameters (insulin, FFA, SOD, GSH-Px, MDA, NO) were determined before and after treatment. Streptozotocin -induced diabetic rat model and human HUVECs cells were applied to assess the anti-oxidative capacity of DJC and its bioactive constituents. The expression levels of eNOS, JNK, GRP78, CHOP, Bcl2, and BAX were measured by qPCR and/or immunoblotting. Results: Diabetic macroangiopathy were ameliorated by DJC administration. Radix pseudostellariae (RP) mediated the anti-oxidative stress capacity of DJC, which improved insulin resistance (p < 0.01) and relieved oxidative stress (p < 0.01) of vascular endothelium through oxidative stress signaling and apoptosis pathway. The ability of DJC to ameliorate diabetic macroangiopathy and relieve oxidative stress was mainly mediated by its bioactive constituent RP. Conclusion: This study would provide experimental evidence for DJC in the prevention and treatment of diabetes and diabetic macroangiopathy.